Visual Gender Representation in Indonesian Language Textbooks of the Merdeka Curriculum for Primary Schools - Tri Ismiyati; Akbar Al Masjid; Ana Fitrotun Nisa; Banun Hafivah Cahyo Khosiyono; Berliana Henu Cahyani (AL-ISHLAH: Jurnal Pendidikan, 2025)
Textbooks play a crucial role in shaping children's perceptions of gender from an early age. As primary sources of learning, visual representations within textbooks can either reinforce or challenge gender stereotypes. This study investigates the portrayal of gender in Indonesian language textbooks used in the Merdeka Curriculum for primary schools. Using a qualitative visual content analysis based on the Brugeilles and Cromer framework, this study examines two government-published Indonesian language textbooks for Grades III and IV. The analysis focuses on three key aspects: the frequency of male and female characters, their occupations, and depicted activities. Visual data were categorized and quantified to assess patterns of gender representation. Findings reveal persistent gender imbalances in both textbooks. Male characters are more frequently depicted, especially in group settings and public spaces. Male characters also hold more diverse and prestigious occupations, while female characters are more often associated with domestic roles and emotional expression. Although the Grade IV textbook shows slightly improved balance in occupational representation, gender stereotypes remain evident in activity types and settings. These patterns suggest that gender bias continues to be embedded in educational materials, despite the progressive aims of the Merdeka Curriculum. The findings call for greater attention to gender-sensitive illustration practices and the development of inclusive learning resources. Teachers are encouraged to critically engage with textbook content and promote discussions on gender equality in the classroom.